EXPERIENCES OF FAMILIES CARING FOR THE ELDERLY WITH DEMENTIA: SCOPING REVIEW - Ronnel D. Dela Rosa; Astuti, Reini (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. The increase in life expectancy of the elderly continues to increase, which has implications for the increase in the incidence of Alzheimer's dementia in the elderly. The elderly with Alzheimer's dementia will experience changes that cause them elderly to be different from their previous personality and behaviour. This will be a burden for the family.This study was to obtain an overview of families' experiences in caring for the elderly with Alzheimer's dementia. Methods.The studyused is a scoping with conducting a focusing review with the PEOS framework (Population, Exposure, Outcome and Study Design), conducting literature searching using relevant databases. Select relevant studies, perform data extraction, analyze and report results. PRISMA Flowchart (Preferred Reporting Items for systematic reviews and Meta-Analyses) was used to describe the literature search flow about experiences of families caring for the elderly with dementia. Results & Analysis. Eight (8) literatures were selected, and positive and negative themes emerged. The upbeat theme is that religious and cultural beliefs patiently cause families to care for the elderly with Alzheimer's dementia. While the negative themes that emerged were Caregiver experiences (emotional and psychological), Loss and stress. Discussion. The most common theme in this study is a negative theme, so it is necessary to be aware of the importance of mentoring and support assistance for families who care for the elderly with dementia.